The Human Body and the Corporeal Novel. An Analysis of Olga Tokarczuk's Flights. - Skikaite, Izabele (E|C, 2023)
This article examines how corporeality (content plane) can explain its expression plane in O. Tokarczuk’s novel Flights. It consists of fragments of different genres narrating distinct stories. However, all of them involve various types of bodies: bodies in motion, sick or dying bodies and fixed body specimens. By attempting to resolve the axiological conflict between the valorization of dynamics (traveling bodies) and statics (admiration of body specimens), the novel’s coherence is revealed. The semantic universe of Flights’s is described by the category of integrality/disintegration. All characters seek to maintain their body integrity (kept by motion) and avoid its fragmentation (resulting from reduced mobility) and disintegration caused by death. This category and the recurrent corporeal relationships explain the novel’s expression plane: Flights’s composition resembles a particular body composed of interacting organs-like stories, and the isolated body specimens-like fragments.